In vitro comparison of physical, chemical, and mechanical properties of graphene nanoplatelet added Angelus mineral trioxide aggregate to pure Angelus mineral trioxide aggregate and calcium hydroxide - Kucukyildiz, Elif Nihan; Dayi, Burak; Altin, Serdar; Yigit, Oktay (Wiley, 2021)
It is important to cover the pulp surface with a biocompatible material that is physically, mechanically, and chemically adequate. Graphene has the potential to form hard tissue, but at high doses, it shows toxic effects. It can be added to biocompatible materials at low doses to enhance their hard tissue forming potential. The aim of this study was to compare the physical, chemical, and mechanical properties of graphene nanoplatelet (GNP) added Angelus mineral trioxide aggregate (A-MTA) to pure A-MTA and calcium hydroxide. Homogeneous mixtures (created by adding +0.1 weight[wt]% and 0.3 wt% GNP to A-MTA), pure A-MTA, and Dycal were used. Three disc-shaped samples of each material were prepared using Teflon mold. Scanning electron microscope-energy dispersive X-ray (SEM-EDX), particle size, microhardness, and Fourier transform infrared spectroscopy (FTIR) analysis of the materials were performed in vitro. Data were analyzed using Kruskal-Wallis test followed by Conover test (p < .001). A-MTA and GNP added samples showed similar peaks in FTIR analysis. In the EDX analysis, the amount of carbon was observed with a higher increase at A-MTA + 0.3 wt% GNP than A-MTA + 0.1 wt% GNP. In the SEM image, hollow structure and particle size decreased as the amount of GNP increased; particle size was smaller at A-MTA + 0.3 wt% GNP than A-MTA + 0.1 wt% GNP (p < .001). A-MTA + 0.3 wt% GNP showed the highest microhardness while Dycal showed the lowest microhardness. The addition of GNP, a material with high potential for forming hard tissue, to the structure of capping materials can also positively contribute to the microhardness of the capping materials.
Keywords: Angelus MTA; FTIR; graphene nanoplatelet; microhardness; SEM– EDX